2008
DOI: 10.1128/jb.00009-08
|View full text |Cite
|
Sign up to set email alerts
|

IS 6110 , a Mycobacterium tuberculosis Complex-Specific Insertion Sequence, Is Also Present in the Genome of Mycobacterium smegmatis , Suggestive of Lateral Gene Transfer among Mycobacterial Species

Abstract: IS6110 is an insertion element found exclusively within the members of the Mycobacterium tuberculosis complex (MTBC), and because of this exclusivity, it has become an important diagnostic tool in the identification of MTBC species. The restriction of IS6110 to the MTBC is hypothesized to arise from the inability of these bacteria to exchange DNA. We have identified an IS6110-related element in a strain of Mycobacterium smegmatis. The presence of IS6110 indicates that lateral gene transfer has occurred among m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 23 publications
1
60
0
1
Order By: Relevance
“…Since different M. tuberculosis strains have different copy numbers of IS6110 and in different regions, this test can be used to distinguish between members of the Mycobacterium tuberculosis complex (MTBC). However, recent studies have demonstrated that this insertion sequence is not exclusive to MTBC, as a similar sequence has been found in the non-pathogenic Mycobacterium smegmatis [6]. PCR of the virulence determining gene devR is also used to identify pathogenic M. tuberculosis, and has been found to be equivalent in sensitivity to IS6110 PCR [7].…”
Section: Diagnosis Of M Tuberculosismentioning
confidence: 96%
“…Since different M. tuberculosis strains have different copy numbers of IS6110 and in different regions, this test can be used to distinguish between members of the Mycobacterium tuberculosis complex (MTBC). However, recent studies have demonstrated that this insertion sequence is not exclusive to MTBC, as a similar sequence has been found in the non-pathogenic Mycobacterium smegmatis [6]. PCR of the virulence determining gene devR is also used to identify pathogenic M. tuberculosis, and has been found to be equivalent in sensitivity to IS6110 PCR [7].…”
Section: Diagnosis Of M Tuberculosismentioning
confidence: 96%
“…strain JLS. The presence of IS6110 in a non-M. tuberculosis complex species is indicative of genetic exchange between the mycobacterial species (Coros et al, 2008).…”
Section: Insertion Sequencesmentioning
confidence: 99%
“…Any mutation in InhA sequences makes changes in INH target and makes the bacteria resistant to isoniazid (19,20).…”
Section: Introductionmentioning
confidence: 99%